Solomon Islands Growth Prospects : Constraints and Policy Priorities - Discussion Note - World Bank (World Bank, 2012)
Economic growth in Solomon Islands since the end of civil conflict in 2003 has been driven by rapid expansion of the forestry sector and large increases in international aid flows. Stocks of natural forest logs are nearing exhaustion and, as the security situation improves, aid flows are likely to flatten off. The Solomon Islands Government asked the World Bank to investigate future growth prospects. This note summarizes the findings and presents a strategic vision for future growth, equity and stability. Efforts have been made to align this work with the policy commitments of the new government. Once these findings and proposals have been considered by the new Government, along with donor partners, specific aspects of these proposals could be further elaborated in subsequent work.